Transmission risk behaviour at enrolment in participants in the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial. (April 2015) - Rodger, AJ; Lampe, FC; Grulich, AE; Fisher, M; Friedland, G; Phanuphak, N; Bogner, JR; Pereira, LC; Rietmeijer, C; Burman, W; Phillips, AN; ,
Abstract : Objectives: A proportion of HIV‐positive people have condomless sex. Antiretroviral treatment (ART) reduces infectiousness, but a substantial proportion of HIV‐diagnosed people are not yet on ART. We describe baseline self‐reported risk behaviours in ART‐naïve Strategic Timing of AntiRetroviral Treatment (START) trial participants. Methods: All START participants completed a risk behaviour questionnaire. Data were collected on sociodemographics, lifestyle factors, health and wellbeing status and clinical status. Recent sexual behaviour and HIV transmission beliefs in the context of ART were also assessed. The primary interest was in condomless sex with serodifferent partners (CLS‐D) in the past two months. Results: A total of 4601 of 4685 HIV‐positive participants (98%) completed the questionnaire [2559 men who have sex with men (MSM), 803 heterosexual men and 1239 women]. Region of recruitment was Europe/Israel, 33%; South America/Mexico, 25%; Africa, 22%; other, 21%. Median age was 36 years [interquartile range (IQR) 29, 44 years]. Forty‐five per cent reported white ethnicity and 31% black ethnicity. Two per cent had HIV viral load < 50 HIV‐1 RNA copies/mL. Seventeen per cent (767 of 4601) reported CLS‐D; 20% of MSM compared with 10% of heterosexual men and 14% of women. MSM were also more likely to report multiple CLS‐D partners. Possible risk limitation measures (reported by more than half of those who had CLS‐D) were seropositioning (receptive anal CLS‐D only) or withdrawal (insertive anal CLS‐D always without ejaculation). CLS‐D was more commonly reported by participants from South America/Mexico and North America compared with Europe; among heterosexual men and women CLS‐D was also more commonly reported among participants from Africa compared with Europe. Knowledge of ART impact on transmission risk was low. Conclusions: A substantial minority recruited to the START study reported CLS‐D at baseline. CLS‐D reporting was higher in MSM than heterosexuals and varied significantly according to region of recruitment. A substantial proportion of MSM reporting CLS‐D appear to take transmission risk limitation measures.